How To Improve Service Performance of Commuterline in Jabodetabek: A Case Study of Depok to Jakarta Kota Route - Budi Sugiarto Waloeya; Imma Widyawati Agustin (Institut Teknologi Sepuluh Nopember, 2017)
DKI Jakarta as the capital of Indonesia is the region with the highest population density in Indonesia caused the spread of population to neighboring areas such as Bogor, Depok, Tangerang and Bekasi. Highly movement in the Greater Jakarta area resulting congestion problems, and one of the transportations that can carry large capacity with highly speed is Commuterline Jabodetabek. As the highly demand of people who use Commuterline Jabodetabek, KCJ Company needs to be accompanied by improved quality of service. The purpose of the study is to determine the service performance of Commuterline and its infrastructure and determine the direction of services performance improvement for Commuterline. Service performance is divided into two kinds: Commuterline as a moda and Station such as security, safety, regularity, comfort, convenience and equality aspects used Importance Performance Analysis (IPA). The results of service then becomes an input in the determination of alternative repair used Analytical Hierarchy Process (AHP). The results showed that there are eight aspects that must be corrected for commuterline such as information and health facilities, information and safety facilities, security guards, security facility, punctuality of travel, seating and space for standing passengers, information of travel disruption and facilities for passengers with disabilities. The highest priority to improve service performance is the use of sensors on the door of commuterline.